ON THE FORMATION OF PROFESSIONAL COMPETENCE IN CADETS THROUGH THE TEACHING OF THE SUBJECT OF RUSSIAN MATHEMATICS IN INSTITUTIONS OF HIGHER MILITARY EDUCATION - Raxmanov I. Ya.; Khalilayev B. T. (Scholars Digest Publishing, 2023)
Through the teaching of higher mathematics in higher military educational institutions, opinions and reflections on the role of competence in the formation of the abilities of cadets to independently think and make unconventional decisions, increasing scientific worldviews and mathematical modeling, its implementation and planning of military actions are discussed in this article.
Keywords: competence, intuition, optimal, model, sphere, map, model classification.